2022
DOI: 10.3389/fbioe.2022.1025076
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional lignin-poly (lactic acid) biocomposites for packaging applications

Abstract: Lignin is the most abundant aromatic biopolymer with many promising features but also shortcomings as a filler in polymer blends. The main objective of this work was to improve the processability and compatibility of lignin with poly (lactic acid) (PLA) through etherification of lignin. Commercial kraft lignin (KL) and oxypropylated kraft lignin (OPKL) were blended with PLA at different weight percentages (1, 5, 10, 20, and 40%) followed by injection molding. Low lignin contents between 1 and 10% generally had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 54 publications
3
13
2
Order By: Relevance
“…Furthermore, a recent prediction from Lin et al, proposed T g values for various amorphous systems and the obtained T g value exhibited an error value of around 20.5°C. Therefore, considering the predicted value of pure PLA is 359.5 K (86.4°C) which is consistent with the values obtained from our experimental value of 46.29°C and literature values of around 60°C by taking into account with the error, around 20.5°C ( Kim et al, 2017 ; Esakkimuthu et al, 2022a ). Moreover, the trend observed from the simulation for all T g values associated with the different wt% can be correlated directly to the experiments.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, a recent prediction from Lin et al, proposed T g values for various amorphous systems and the obtained T g value exhibited an error value of around 20.5°C. Therefore, considering the predicted value of pure PLA is 359.5 K (86.4°C) which is consistent with the values obtained from our experimental value of 46.29°C and literature values of around 60°C by taking into account with the error, around 20.5°C ( Kim et al, 2017 ; Esakkimuthu et al, 2022a ). Moreover, the trend observed from the simulation for all T g values associated with the different wt% can be correlated directly to the experiments.…”
Section: Resultssupporting
confidence: 92%
“…We obtained a Young’s modulus value of 1,400 MPa for PLA, which is lower than our previously proposed value of approximately 2,100 MPa ( Esakkimuthu et al, 2022a ). It has been noted that the mechanical properties of composites are significantly influenced by the processing methods employed during fabrication.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The small peak at 3670 cm −1 experienced by Fraun-Org, Acid-Org, and Phenol-AH is attributed to free hydroxyl groups that are not involved in hydrogen bonding and are quite common in lignin. 37 These free hydroxyl groups could be a side product from the cleavage of ether linkages during the extraction process. Organosolv lignin, however, is extracted through the dissolution of lignin under relatively milder conditions in organic solvents, sometimes with the addition of a base or an acid.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Esakkimuthu et al synthesized a composite material of poly­(lactic acid)/lignin, which has the ability to effectively absorb UV light. This property makes it suitable for preventing food oxidation and decomposition when used in food packaging materials . The gas barrier, antioxidant activity, and biodegradability of PHB/PHA films were significantly enhanced by incorporating lignin into PHB/PHA films, as demonstrated by Vostrejs et al The lignin-zinc oxide (LZn) hybrid particles, prepared by Xiao et al, demonstrated a strong ability to kill Escherichia coli (E.…”
Section: Introductionmentioning
confidence: 99%